P100 Long term obstetric outcomes after less radical fertility sparing treatment in patiens with small volume stage i cervical cancer. (1st November 2019) - Rob, L; Robova, H; Halaska, MJ; Hruda, M; Drozenova, J; Pichlik, T; Pluta, M
Abstract : Introduction/Background: The purpose of the study is to present our clinical experience, pregnancy management and long term obstetrical outcome after less radical fertility sparing surgery SLNM + laparoscopic lymphadenectomy + simple trachelectomy or large recone. Methodology: From 1999–2018, 91 women with squamous or adenocarcinoma with tumor less than 20 mm in the largest diameter and infiltration less than half of cervical stroma underwent laparoscopic SLNI and select extirpation of afferent parametrial channel and frozen section (FS) of SLN and laparoscopic pelvic lymphadenectomy or only SLN. Second step is simple trachelectomy without cerclage or large recone. Results: Fertility was definitely spared in 76 women. 3 women (3.3%) not plan pregnancy, 9 currently plan pregnancy in future (9.9%), 64 women (84.2%) wish to be pregnant and 53 was pregnant (82.8%). From 76 fertility spared, 53 was pregnant - pregnancy rate 69.7%, 44 women have 50 baby - delivery rate was 57.9%. 37 was term pregnancy (74%), extreme premature 24–27w - 2 baby (4%), premature (28–32w) - 2 baby (4%), premature (33–37w) - 9 baby (18%). 22 unsuccessful pregnancy (5 artericial abortion, 11 spontaneus abortion in 1 trimestr, 4 spontaneus abortion in 2 trimestr, 2 GEU. Two women after hysterectomy have two baby with donor mother. Conclusion: SLNM and laparoscopic pelvic lymphadenectomy with simple trachelectomy or large recone in small volume cervical cancer (less than 2cm in the largest diameter and less than half of stromal invasion) have excellent pregnancy result. This work was supported by Charles University research program PROGRES Q 28 (Oncology). Disclosure: Nothing to disclose.